Mitochondria Fusion upon SERCA Inhibition Prevents Activation of the NLRP3 Inflammasome in Human Monocytes - Pereira, Ana Catarina (2022)
Sarco/endoplasmic reticulum Ca2+ ATPase (SERCA) is a crucial component of the cellular machinery responsible for Ca2+ homeostasis. The selective inhibition of SERCA by thapsigargin (TG) leads to perturbations in Ca2+ signaling, which can trigger endoplasmic reticulum (ER) stress. The unfolded protein response (UPR) pathway is activated in response to ER stress and induces an adaptive response to preserve cell survival or committee cells to programmed death, depending on stress duration and/or level. Early stages of ER stress stimulate mitochondrial metabolism to preserve survival but under chronic ER stress conditions, mitochondrial dysfunction is induced, which, in turn, can enhance inflammation through NLRP3 inflammasome activation. This study was aimed at investigating the role of SERCA inhibition on NLRP3 inflammasome activation in human monocytes, which was evaluated in primary monocytes isolated from healthy individuals and in the THP-1 human monocytic cell line. Findings obtained in both THP-1 and primary monocytes demonstrate that SERCA inhibition triggered by TG does not activate the NLRP3 inflammasome in these innate immune cells since IL-1β secretion was not affected. Results from THP-1 monocytes showing that SERCA inhibition increases mitochondrial Ca2+ content and fusion, in the absence of changes in ROS levels and membrane potential, support the view that human monocytes counteract ER stress that arises from inhibition of SERCA through modulation of mitochondrial morphology towards mitochondria fusion, thus preventing NLRP3 inflammasome activation. Overall, this work contributes to a better understanding of the molecular mechanisms that modulate the activity of the NLRP3 inflammasome leading to sterile inflammation, which are still poorly understood.